Correlation of Learning Motivation Based on ARCS Model With English Achievement of Midwifery Students - Hariyanto, Hariyanto; Joyoatmojo, Soetarno; Nurkamto, Joko; Gunarhadi, Gunarhadi (Bina Nusantara University, 2019)
This research aimed at analyzing the correlation between learning motivation and the English achievement of Midwifery students. The research was conducted at Midwifery Academy of Harapan Mulya Ponorogo, East Java, Indonesia. The respondents were 39 students. Data were collected through motivational questionnaires adopted from the ARCS Keller’s model, namely Course Interest Survey (CIS), and Instructional Materials Motivation Survey (IMMS). The English achievement was obtained from the score of the final exam with the correlation analysis used was Pearson Product Moment. The result of the statistical test of the correlation between learning motivation based on students’ perception of the Instructor-led instruction and English achievement showed the level of significance that was 0,008<0,05 with coefficient correlation 0,431. The correlation of learning motivation based on students’ perception toward instructional materials with English achievement showed the correlation coefficient that was 0,349 with significance level 0,029<0,05. The result shows that there is a significant correlation between learning motivation and English achievement. The researchers suggest that the lecturers improve the motivation of students’ learning through improving lecturers’ competencies in teaching, using appropriate learning methods, and teaching materials that are in accordance with the field of student interest in learning.